Editorial: can serum triiodothyronine‐to‐thyroxine (T3/T4) ratio predict safety and efficacy of biologic treatment in IBD?. Issue 2 (25th December 2020) - Carbery, Isabel; Selinger, Christian P.
Abstract : LINKED CONTENT This article is linked to Bertani et al papers. To view these articles, visit https://doi.org/10.1111/apt.16167 and https://doi.org/10.1111/apt.16213